Nepal on the IFLA Library Map of the World - Mandl, Helen; Pabērza Ramiresa, Kristīne (Access: An International Journal of Nepal Library Association, 2022)
IFLA’s Library Map of the World, launched in response to the need to accurately collect and share basic data and information about the library landscape in each country, has grown into a powerful advocacy tool providing access to country-level library statistics from more than 130 countries in the world, full country profiles describing the library field in each country, and SDG stories about impactful library programmes contributing to the Sustainable Development Goals. Nepal has engaged in the LMW project with library data covering all library types and a full country profile containing information about the library environment in Nepal, including organisations and institutions in the library field, policy and legislation documents, and information about education and events for library professionals. Nepal's presence can be strengthened by adding SDG stories highlighting the contribution that libraries around the country are making to the country’s development. During the last five years since Nepal joined the LMW project, the country has demonstrated an increase in its data availability that is higher as the regional average in Asia-Oceania region. The article outlines the benefits to the library field in Nepal from its involvement and visibility in this project and offers suggestions for using high-quality library data to demonstrate the value libraries bring to their communities and achievement of the country’s development goals.